Isolation and Characterization of Hypolipidemic Compound from Cajanus cajan (TAJ: Journal of Teachers Association, 2011)
The study was carried out to identify the compound responsible for hypolipidemic and hypoglycemic effects of Cajanus cajan (redgram). The methanol extract of redgram seeds was found to decrease fasting blood glucose and lipid profile (p